2015
DOI: 10.1111/jvim.13657
|View full text |Cite
|
Sign up to set email alerts
|

A Placebo‐Controlled, Prospective, Randomized Clinical Trial of Polyethylene Glycol and Methylprednisolone Sodium Succinate in Dogs with Intervertebral Disk Herniation

Abstract: BackgroundAcute intervertebral disk herniation (IVDH) is a common cause of spinal cord injury in dogs and currently there is no proven medical treatment to counter secondary injury effects. Use of methylprednisolone sodium succinate (MPSS) or polyethylene glycol (PEG) as neuroprotectants is advocated but controversial because neither treatment has been tested in placebo‐controlled, randomized, blinded trials in dogs.HypothesisPolyethylene glycol will improve the outcome of severe spinal cord injury caused by I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
70
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 52 publications
4
70
0
4
Order By: Relevance
“…Another limitation of the current study is the lack of longer term follow‐up data beyond 6 weeks postoperatively, as some dogs that were nonambulatory at 6 weeks could have gone on to recover ambulatory function in the longer term. However, previous studies have shown that the majority of postoperative functional recovery after SCI in dogs occurs within 4–8 weeks of surgery, supporting this observation time frame 11, 13, 32, 42. To maximize the outcome data available, we used 2 functional scoring systems postsurgery; an ordinal 12‐point score (OFS) and a treadmill‐based gait score (RI), both described and validated previously 31, 35.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Another limitation of the current study is the lack of longer term follow‐up data beyond 6 weeks postoperatively, as some dogs that were nonambulatory at 6 weeks could have gone on to recover ambulatory function in the longer term. However, previous studies have shown that the majority of postoperative functional recovery after SCI in dogs occurs within 4–8 weeks of surgery, supporting this observation time frame 11, 13, 32, 42. To maximize the outcome data available, we used 2 functional scoring systems postsurgery; an ordinal 12‐point score (OFS) and a treadmill‐based gait score (RI), both described and validated previously 31, 35.…”
Section: Discussionmentioning
confidence: 78%
“…All dogs underwent imaging and decompressive surgery, followed by a prescribed standardized home physical therapy plan and strict rest, as is standard protocol at the study institution. As neither trial demonstrated an effect of treatment over placebo, all dogs followed at NCSU were included in this study (from the first trial—MPSS: n = 6, PEG: n = 6, saline: n = 5, and from the second trial—cranberry: n = 32, placebo: n = 35) 32, 33. For each dog, age, breed, sex and body weight were recorded, as well as duration of clinical signs, any preoperative medication administered by the referring veterinarian, IVDE site and ordinal functional grade (modified Tarlov grade: grade 1 = neurologically normal, grade 2 = ambulatory paraparesis, grade 3 = nonambulatory paraparesis, grade 4 = paraplegia with intact conscious pain perception, grade 5 = paraplegia with absent conscious pain perception) at presentation 34.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Steroids are no longer considered to be beneficial and may be contraindicated in the management of acute and chronic IVDH (Hurlbert 2000, Levine and others 2007, Olby and others 2016). …”
Section: Non-surgical Managementmentioning
confidence: 99%
“…A glance through recent issues of the Journal of Veterinary Internal Medicine identifies prospective randomized clinical trials (RCTs) involving dogs,1, 2, 3, 4, 5, 6, 7, 8, 9 cats,10, 11, 12, 13 cows,14, 15 and horses16, 17 that cover the fields of neurology,1, 8 oncology,3, 5 cardiology,4, 6, 12 and internal medicine 2, 9, 10, 11, 13, 14, 15, 16, 17. Collectively, these findings suggest that we have entered into an era of prospective veterinary RCTs.…”
mentioning
confidence: 99%